Utilization of sage by-products as raw material for antioxidants recovery—Ultrasound versus microwave-assisted extraction - Zeković, Zoran; Pintać, Diandra; Majkić, Tatjana; Vidović, Senka; Mimica-Dukić, Neda; Teslić, Nemanja; Versari, Andrea; Pavlić, Branimir (Industrial crops and products, 2017)
•Utilization of sage herbal dust as raw material for extraction of phytochemicals.•Evaluation of ultrasound and microwave extraction effects on polyphenols extraction.•Significant improvements in yields of extracted polyphenols were obtained.•In vitro assessment of antioxidant activity in obtained extracts.•Optimization of the process using RSM approach and validation was performed. In this work, sage (Salvia officinalis L.) by-products from filter tea factory, i.e. sage herbal dust, was valorized as raw material for extraction of phenolic antioxidants. Ultrasound-assisted (UAE) and microwave-assisted extraction (MAE) of polyphenols from sage herbal dust were separately optimized by simultaneous maximization of total phenols (TP) and total flavonoids (TF) yields. Box-Behnken experimental design and response surface methodology (RSM) was used for extraction optimization. In case of UAE, temperature (40, 60 and 80°C), extraction time (40, 60 and 80min) and ultrasonic power (24, 42 and 60W/L) were independent variables, while optimized MAE parameters were ethanol concentration (40, 60 and 80%), extraction time (10, 20 and 30min) and liquid to solid ratio (20, 30 and 40mL/g). Antioxidant activity of sage extracts was determined by DPPH, FRAP and superoxide anion radical neutralization assays, and good correlation between polyphenols content and antioxidant activity was observed. According to results, it could be concluded that novel extraction techniques (UAE and MAE) provided significant advantages for recovery of sage polyphenols comparing to traditional methods.